Penerapan Model Based Learning pada Mata Pembelajaran PPKn di Kelas X A Madrasah Aliyah Ihyaul Islam untuk Meningkatkan Kemampuan Berfikir Kritis Siswa - Dzaky Isyuniandri; Ani Anjarwati; Balqhis Nabila Samputry; Shafa Azreena Madani Fitry; Sri Wahyuningsih; Adinda Puspita Cecilia (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2026)
This study aims to improve students’ critical thinking skills through the implementation of the Problem-Based Learning (PBL) model in Pancasila and Civic Education (PPKn), particularly on Human Rights material, among Grade X students at Madrasah Aliyah Ihyaul Islam. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart spiral model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 36 Grade X students. Data were collected through classroom observations, critical thinking tests, interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña qualitative analysis model, including data reduction, data display, and conclusion drawing. The findings indicate that the PBL model effectively enhanced students’ critical thinking skills in a gradual manner. Prior to the intervention, most students showed low abilities in identifying problems, analyzing information, constructing arguments, drawing conclusions, and proposing solutions. In Cycle I, students demonstrated moderate improvement, although their analytical depth and argument quality were still limited. Further improvement occurred in Cycle II, where students achieved good and very good levels of critical thinking. This progress was reflected in higher participation during learning activities, stronger arguments supported by facts and legal foundations, and a better ability to connect Human Rights concepts with real-life cases. Therefore, the study concludes that the Problem-Based Learning model is effective in improving critical thinking skills in PPKn learning.